Enhanced Localization of Recurrent Parathyroid Carcinoma Using 99mTc-MIBI SPECT/CT: A Case Report (Bangladesh Journal of Nuclear Medicine, 2026)
Parathyroid carcinoma (PC) is a rare endocrine malignancy, representing less than 1% of primary hyperparathyroidism cases. Its management is particularly challenging due to the high incidence of local recurrence. Detailed mapping of tumor location requires imaging modalities. Hybrid imaging SPECT/CT is widely regarded as the preferred imaging technique for localizing both primary and recurrent parathyroid tumors prior to surgical intervention. Here, we report the case of a 24 year old male with hyperparathyroidism due to recurrent parathyroid carcinoma. Patient had history of radical neck surgery four times. Each time, preoperative localization of the recurrent mass was successfully achieved using 99mTc-MIBI SPECT/CT.Bangladesh J. Nuclear Med. 28(2): 359-363, July 2025